Determinação de resíduos dos pesticidas pirimetanil, pirimicarbe e buprofezina em águas ambientais por SPME e GCMS - Silva Filho, Clóvis Fernandes da (2009)
The aim of the work was to develop method for determining pyrimethanil, pirimicarb and buprofezin residues in environmental water using solid-phase microextraction and gas chromatography-mass spectrometry. To perform the SPME, a 100 μm polydimethylsiloxane (PDMS) fiber was used for the extraction of the pesticides from water samples. Using univariate optimization process, the main factors affecting the SPME process, such as saline concentration (0 %), stirring rate (900 rpm), pH effect (6.0) and desorption time (7 min.) were studied. The method was validated for the pesticides and the intermediate precision (< 15 %) was shown to be satisfactory. The detection and quantification limits ranged from 0.058 to 0.231 ng L−1. The linearity was studied in the range of 0.1 - 4.0 μg L−1 obtaining good correlation coefficients (> 0.991). The results obtained in the validation of SPME-GC-MS for the determination of 3 pesticides in water showed that the method is fast, simple, sensitive and very useful in routine laboratories. The developed method has been used to monitor pyrimethanil, pirimicarb and buprofezin contaminations in superficial water samples collected around irrigated areas of Platô de Neópolis (Neópolis/SE) and Senador Nilo Coelho (Petrolina/PE). The concentrations of buprofezin and pirimicarb ranged from undetectable to 0.013 μg L−1 and 0.20 to 1.0 μg L−1, respectively. Pyrimethanil was not observed in the samples. The concentrations of the pesticides in the real samples were in accordance with European legislation.